The sequential analysis of transgressors’ accounts of breaking environmental laws - Martín, Ana M.; Salazar-laplace, María Esther; Ruiz, Cristina (The Spanish Journal of Psychology, 2008)
Three-hundred and twenty written accounts of environmental transgressors were assessed by sequential analysis to reveal their argument streams. The accounts were obtained from the written statements that transgressors are allowed to give during the Spanish administrative process and which were included in files handled by four environmental law enforcement agencies. These agencies are distributed across national, regional, island and municipality jurisdictions. The setting for the study is a highly protected environment in which environmental laws have high salience. Results reveal that transgressors use simple argument streams, consistently more defensive than conciliatory, and questioning the perceived legitimacy of environmental law. It was seen also that the empirical functioning of the explanations related to pursuing emotional/prosocial objectives differs from what was expected from the traditional conceptual definition. Results are discussed in terms of how the assessment of the internal dynamic of the accounts would provide valuable information on transgressors’ reasoning in relation to environmental laws.